2008
DOI: 10.1007/s11668-008-9141-x
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Location of Acoustic Emissions for a Naturally Degrading Rolling Element Thrust Bearing

Abstract: Acoustic Emission (AE) technology applied to condition monitoring is gaining acceptance as a useful complimentary tool. This article demonstrates the use of traditional AE parameters, the Enegry Index and Kolmogorov-Smirnov test (KS-test) to detect, locate, and monitor natural defect initiation and propagation in a conventional rolling element thrust bearing. To undertake this task a special purpose test-rig was built to allow for accelerated natural degradation of a bearing race. It is concluded that sub-surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The thrust shaft was driven by a hydraulic cylinder (Hi-Force HYDRAULICS- Under normal conditions of load, rotational speed and good alignment, surface damage begins with small cracks, located between the surface of the flat track and the rolling elements, which gradually propagate to the surface generating detectable AE signals. Elforjani et al [10] employed the following theories to determine the test duration to the onset of surface fatigue: Hertizan theory for determining surface stresses and deformations [11], Thomas and Hoersh theory for sub-surface stress [11], and, the Lundberg and Palmgren theory for fatigue evaluation [12]. For the grooved race the standard procedure for determining dynamic load rating, as described by BS (British Standards Documents) 5512; 1991, was employed.…”
Section: Test-rig Design and Layoutmentioning
confidence: 99%
“…The thrust shaft was driven by a hydraulic cylinder (Hi-Force HYDRAULICS- Under normal conditions of load, rotational speed and good alignment, surface damage begins with small cracks, located between the surface of the flat track and the rolling elements, which gradually propagate to the surface generating detectable AE signals. Elforjani et al [10] employed the following theories to determine the test duration to the onset of surface fatigue: Hertizan theory for determining surface stresses and deformations [11], Thomas and Hoersh theory for sub-surface stress [11], and, the Lundberg and Palmgren theory for fatigue evaluation [12]. For the grooved race the standard procedure for determining dynamic load rating, as described by BS (British Standards Documents) 5512; 1991, was employed.…”
Section: Test-rig Design and Layoutmentioning
confidence: 99%
“…Despite of the success of vibration-based methodologies, over the last decades bearing condition monitoring techniques based on Acoustic Emission (AE) have become very popular [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. AE has demonstrated to be a very powerful tool for fault detection and diagnosis particularly in bearings, and some recent studies [13; 32; 33] reported that AE can be more sensitive in detecting incipient faults in bearings over other methodologies based on vibration data.…”
Section: Condition Monitoring Of Bearings Based On Acoustic Emissionmentioning
confidence: 99%
“…Under normal conditions of load, rotational speed and good alignment, surface damage begins with small cracks, located between the surface of the flat track and the rolling elements, which gradually propagate to the surface generating detectable AE signals. The procedure employed to determine the test duration to the onset of surface fatigue has been previously described by Elforjani et al [10] and involved the Hertizan theory for determining surface stresses and deformations [11], Thomas and Hoersh theory for sub-surface stress [11], and, the Lundberg and Palmgren theory for fatigue evaluation [12].…”
Section: Figure 3 Schematic Of the Data Acquisition Systemsmentioning
confidence: 99%